Controlling GDP and Debt with a Post-Keynesian model - Domenicos, Charalampos-Anastasios; Kotsios, Stelios (International Conference on Business and Economics - Hellenic Open University, 2023)
Our aim in this paper is to design a set of fiscal policy rules using a linear, discrete macroeconomic Post-Keynesian model with delays. We develop algebraic methods with appropriate symbolic algorithms that produce a solution, which allows us to find a path for the desired GDP and debt targets to be met. Keywords: Fiscal policy, Symbolic algorithmic methods, GDP, Debt, Algorithmic control JEL Classification: E00, E62, E12